Multicenter evaluation of the antimicrobial activity for seven broad-spectrum beta-lactams in Turkey using the Etest method - (:unkn) unknown (ELSEVIER SCIENCE INC, 1999)
From March through July 1997, a nine laboratory surveillance project was initiated in Turkey to monitor the potency and spectrum of seven broad-spectrum antimicrobial agents (cefepime, ceftazidime, cefotaxime, imipenem, aztreonam, cefoperazone/sulbactam, and ticarcillin/clavulanate) tested against approximately 100 organisms (average 82; range 70 to 95 isolates) per participant center (736 strains). Eleven groups of organisms were tested by the Etest method (AB BIODISK, Solna, Sweden) with results validated by concurrent quality control strain analysis. Results front all centers were tabulated and 91.1% of quality assurance tests were within ranges recommended by the National Committee for Clinical Laboratory Standards. Among the seven beta-lactam-class drugs tested, imipenem and cefepime were the most active beta-lactams tested against all isolates. Overall, the rank order of susceptibility of the seven agents was imipenem > cefepime > cefoperazone/sulbactam > ceftazidime > cefotaxime > aztreonam > ticarcillin/clavulanate. Both cefepime and imipenem were active against ceftazidime-resistant strains of Enterobacteriaceae as well as against Streptococcus spp, and oxacillin-susceptible Staphylococcus aureus. Resistance phenotypes consistent with extended spectrum beta-lactamases were documented among Escherichia coli and Klebsiella spp., and profiles consistent with stably derepressed Bush-Jacoby-Mederios group 1 (Amp Ci cephalosporinases were common among Enterobacter spp., Citrobacter spp., and Serratia spp. These data should be used to guide empiric therapy with beta-lactams in Turkey, and additionally will provide a reference statistical baseline to which future national studies of drugs in this class can be compared. (C) 1999 Elsevier Science Inc.
Keywords: IN-VITRO ACTIVITY; UNITED-STATES; MEDICAL-CENTERS; CEFEPIME; CEPHALOSPORINS; CEFTAZIDIME; RESISTANT; EFFICACY; PATHOGENS; FK-037